Land Acquisition Act 1960: a study on compensation for compulsory acquisition / Amira Md Zain, Nurdiana Zainal Azaha and Nor Emellia Mohd Sharif - Md Zain, Amira; Zainal Azahar, Nurdiana; Mohd Shariff, Nor Emellia (2012)
Land acquisition involves the compulsory taking of land, often against the will of the landowners. The law in Malaysia requires the state to pay compensation adequately however, adequate compensation is not defined in the statute. Thus, we foresee the importance of looking in depth of the main legislations governing the assessment of compensation for compulsory acquisition, which is the Land Acquisition Act 1960 that should be read together with Article 13 of the Federal Constitution which laid down the right of the Government to acquire land subjected to adequate compensation and principals laid down under the Aboriginal Peoples Act 1960 for the aborigines. An interview was conducted with the Land Administrator to discover their, views with regard to the above issues. This interview revealed the views that compensation attributes under the stipulated laws are not adequate to fulfill adequate compensation notion under the spirit of Article 13 of Federal Constitution 1957. There is a need to review the heads of compensation structures by incorporating other countries practices such as United Kingdom, Australia, Japan and New Zealand on payment of solatium potential development, injurious affection, reinstatement claim and surveyor's fees as over and above total compensation. In conclusion the Land Acquisition Act 1960 should be more precise in providing a framework in order to avoid any discrepancies of awards decided between Land Administrator and judges in future.